2016
DOI: 10.3390/ani6050027
|View full text |Cite
|
Sign up to set email alerts
|

Basing Turkey Lighting Programs on Broiler Research: A Good Idea? A Comparison of 18 Daylength Effects on Broiler and Turkey Welfare

Abstract: Simple SummaryAltering daylength in a poultry management program is a simple tool that can have immense impacts on productivity and bird welfare. It is not uncommon for lighting data derived from broiler research to be extrapolated to turkey production. This review of two studies (one with broilers and the second with turkeys), completed in the same research facility using the same lighting programs, shows evidence that some, but not all responses to graded daylengths are similar between these two species. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…These findings have important practical aspects, considering the significance of the domestic turkey as meat-producing animal. Schwean-Lardner et al [49] exposed turkeys to different cycles with varying periods of darkness and studied body weight, feed efficiency, skeletal disorders, mortality, mobility, and ocular measures, in birds. Most of these factors achieved their best results in cycles with the shortest days.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important practical aspects, considering the significance of the domestic turkey as meat-producing animal. Schwean-Lardner et al [49] exposed turkeys to different cycles with varying periods of darkness and studied body weight, feed efficiency, skeletal disorders, mortality, mobility, and ocular measures, in birds. Most of these factors achieved their best results in cycles with the shortest days.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting procedures based on manipulating the light program are easier to implement and manage than physical restriction of the access to feed. Consequently, controlling light programs has been the preferred method to control FI in previous research studies ( Buyse et al., 1996 , Schwean-Lardner et al., 2013 , Schwean-Lardner et al, 2016 ). Limited information is available on the effects of physical restriction to access to feed, while maintaining the light program unchanged, on the development of the proximal part of the GIT of birds.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of Schwean-Lardner et al, (2016), Yang et al, (2015) and Aviagen (2014), improved feed conversion efficiency was observed in birds subjected to split darkness when compared to the continuous light group. Intermittent feeding and lighting have been used to improve feed efficiency (Farghly and Hassanien, 2012;Farghly and Makled, 2015).…”
mentioning
confidence: 95%
“…Metwally et al, (2015) reported that light type significantly affected carcass traits. In studies of Schwean-Lardner et al, (2016). Olanrewaju et al, (2012) Indicated that long/continuous and regular/intermittent photoperiod equally improved broiler carcass characteristics compared with short/non-intermittent photoperiod.…”
mentioning
confidence: 99%